Critical Literacy Training to Enhance Teachers' Skills in Designing Deep Learning Activities - Sari, Dwi Rosita; Murtafiah, Wasilatul; Pradana, Lingga Nico; Lien, Hsi-Nancy (Jurnal Abdimas Kartika Wijayakusuma, 2026)
Critical literacy is the ability to actively analyze, question, and evaluate texts, media, and other forms of communication to understand the deeper meanings, power relations, and perspectives behind them. It goes beyond simply reading or comprehending information since it involves thinking about who created the message, why it was created, and whose voices are represented or missing. Ultimately, critical literacy empowers individuals to become thoughtful, informed, and active participants in society, capable of questioning injustice, promoting equality, and making independent, ethical judgments. This community engagement project was conducted in SDN Kenongorejo 02, Madiun in collaboration of Universitas PGRI Madiun dan National Dong Hwa University. This critical literacy is working together with Critical Literacy Platform (CLP). The priority problems are: (1) the low level of teacher and student involvement and participation in efforts to improve literacy quality; (2) the socialization of the program is not carried out optimally for both teachers and students; (3) the lack of understanding of critical literacy among teachers and students; (4) the lack of innovation in learning related to critical literacy. There are two solutions which have been conducted: (1) critical literacy training by international experts as a means of enhancing critical literacy; (2) designing learning activities through the critical literacy platform.